2002
DOI: 10.1191/1358863x02vm439oa
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of nitric oxide to exercise hyperemia in the human forearm

Abstract: The contribution of nitric oxide (NO) to exercise-induced hyperemia is debated. Previous conclusions that nitric oxide synthase (NOS) inhibition reduces endothelium-dependent vasodilation during exercise hyperemia may be confounded by inhibitor-mediated increases in resting vascular tone. In this study, nine healthy participants performed wrist flexion exercise before and during intra-arterial administration of the NOS-inhibitor NG-monomethyl-L-arginine (L-NMMA, 2 mg x min(-1)). Nine additional subjects perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Interobserver variability was not evaluated in the present study, but we have previously reported a coefficient of variation ϳ20% when measuring BA vasodilation in the same subject on multiple visits to the laboratory (21). Finally, we wish to acknowledge that we did not determine blood flow during the recovery period following exercise, which has been reported to differ following L-NMMA administration (13).…”
Section: Impact Of Enos Blockade On Ba Vasodilationmentioning
confidence: 88%
See 1 more Smart Citation
“…Interobserver variability was not evaluated in the present study, but we have previously reported a coefficient of variation ϳ20% when measuring BA vasodilation in the same subject on multiple visits to the laboratory (21). Finally, we wish to acknowledge that we did not determine blood flow during the recovery period following exercise, which has been reported to differ following L-NMMA administration (13).…”
Section: Impact Of Enos Blockade On Ba Vasodilationmentioning
confidence: 88%
“…In contrast, six exercise intensities (ranging from 6 to 64% MVC, Table 2) were used in the present study, producing BA blood flows as high as 600 ml/min in some individuals at the highest exercise intensity. Other previous studies have examined the effects of L-NMMA on exercise hyperemia using strain-gauge plethysmography (9,12,13), which requires the cessation of exercise for the determination of blood flow. The present study thus builds on these previous studies through continuous ultrasound Doppler measurements and the inclusion of wide-ranging exercise intensities to more fully characterize the role of NO during exercise.…”
Section: Impact Of Enos Blockade On Ba Vasodilationmentioning
confidence: 99%
“…Other vasodilator(s) that are involved in local functional vasodilation, such as NO (44), may also be improved following exercising training. For example, NO synthesis and sensitivity have been shown to be elevated following exercise training in both lean and obese subjects (9,12). In addition, the basal and the maximal diameters were not altered by exercise training, suggesting that the increased vasodilator responses are not due to an altered maximal vasodilator capability or vascular anatomy (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…In humans, a number of studies have shown a reduction in FBF during or immediately after exercise in response to nonselective NOS inhibition with L-NMMA or L-NAME (8,10,11,30). However, the size of the effects has been small and, when compared with a vasoconstrictor control with similar There is no significant difference in FBF during L-NMMA or SMTC infusion when compared with saline, for either low-intensity exercise (P ϭ 0.91 and P ϭ 0.44, respectively; n ϭ 10) or high-intensity exercise (P ϭ 0.46 and P ϭ 0.68, respectively; n ϭ 10).…”
Section: Discussionmentioning
confidence: 99%
“…A role for NOS and particularly nNOS in functional sympatholysis is supported by some (1,19,26) but not all (6) animal studies. However, human studies using nonspecific inhibitors of NOS suggest the role of NOS in regulation of blood flow immediately after local exercise is small or absent (7,8,10,11) but have not been performed in the presence of the increased sympathetic activation expected during systemic exercise.…”
mentioning
confidence: 95%